Influence the quality of the interface of online stores on their memorability - Pytka, Katarzyna; Miłosz, Marek (Journal of Computer Sciences Institute, 2020)
The article describes influence the quality of the interface of online stores on their memorability on selected examples. Nielsen heuristics, LUT’s list and mamorability experiment were used in interface quality assesment.